Formación del profesorado en educación musical en la Universidad de Illinois: un estudio de caso - Aróstegui, José Luis (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2004)
This paper reports case studies of music education students at the University of Illinois at Urbana Champaign. Its purpose is to tell of the conditions, causes and ways in which some undergraduate students in music education build both musical and educational knowledge en route to becoming music teachers. My intention is to portray and discuss what these three students experienced during their junior spring semester. I will refer to the concept of music education that each of these three students had. I will interpret each view according to personal and academic characteristics that I found relevant to understand their thinking about music education. I will try to relate those characteristics with other data from the field pertinent to understanding such music education concepts. First I will present a brief introduction to the music education program, then each student’s perception. In the conclusion I will speak of similarities and disparities across cases.